Negotiations as a tool of business strategy creation - Kozina, Andrzej W. (Managerial Economics, 2015)
The objective of the paper is to describe the author’s concept of considering the negotiations between internal stakeholders as a speciﬁc tool for the creation of company’s strategy. Firstly, the deﬁnition of such negotiations is presented, in the context of the general interpretations of negotiations. The most important is their deﬁnition as interactive decision making process. Secondly, speciﬁc features of such negotiations as a tool for business strategy creation are discussed. Two types of those negotiations are distinguished: multiparty and multiply ones. Thirdly, the possible strategies for conducting such negotiations are suggested, according to their two types. Finally, the assessment of proposed concept is presented, i.e. its advantages and disadvantages are listed as well as the directions for further research are pointed out